Validity and Reliability Study: Values Scale for Secondary School Students (VSS) - Didem Cetin; Mustafa Volkan Coskun (ÜNİVERSİTEPARK Limited, 2017)
The purpose of the current study is to develop a data collection tool that can be used to determine the values of secondary school students. The study group consists of 299 students attending secondary schools in the city of Mugla, Turkey, who voluntarily participated in the study. For the construct validity of the scale, exploratory and confirmatory factor analyses were conducted. As a result of the exploratory factor analysis (EFA), a three-factor structure was elicited for the factors of "Sensitivity", "Trustability", and "Responsibility". This three-factor structure together explains 41.11% of the total variance. The scale comprises of 30 items that can be assigned scores ranging from "1 (Never)" to "4 (Always)". When the findings obtained through confirmatory factor analysis (CFA) were evaluated, χ2/df ratio was found to be 2.93. The 30-item, three-factor structure obtained as a result of EFA was also examined using CFA and the results showed that the scale yields good fit values. For the trustability of the scale, item-total correlation and Cronbach's Alpha internal consistency coefficient were analyzed. In conclusion, a valid and reliable scale with adequate psychometric features was developed in order to determine the values of secondary school students (VSS).